A exclusão na inclusão: o direito fundamental à educação das pessoas com deficiência intelectual - Ribeiro, Letícia de Oliveira (2011)
Education combined with other factors become relevant instrument for the intellectual and social growth of the individual, however, throughout history you can see that was offered several times the population in order to meet the aspirations of the ruling classes. Consensus that is indispensable to the emancipation of the individual, the Constitution of 1988 set out to education as a fundamental right, thereby making their observance mandatory. It is for this reason that the state must guarantee the right to education through positive benefits. Given the difficulty in effecting the right to education in regular education networks, it is not difficult to conclude that students with special educational needs are even greater difficulties. In this context, attention to the formal devices that children with intellectual disabilities are included in regular education, but finding the necessary trimmed are excluded in the classroom. This study aimed to identify how the project should be developed emancipatory education for pupils with special educational needs, so that education has the goal of promoting the development of the student, not to satisfy the wishes of the ruling classes. After demonstrating the effectiveness of a chapter on fundamental rights and the difficulties of its implementation, in chapter two, issues relating to inclusive school environment were investigated in chapter three to explain the difference between intellectual disability and mental illness. With the theoretical research completed, it was concluded that students with intellectual disabilities should be included in a mandatory way in the regular education and that the defect that the special educational needs should not be a focus of concern of inclusive education, but awareness of society and professionals involved in the educational project, they need to have the knowledge necessary to meet those needs. Given the formal devices, and developing mechanisms to ensure the inclusion, the education project brings the effective inclusion, whose main concern lies in the emancipation of the individual.